Answer:
Step-by-step explanation:
Answer:
1) 4x^2, 3x, -11y, 17 (4 terms)
2) 4, 3, -11, 17 (4 coefficients)
3) none
Step-by-step explanation:
<span>Assuming the graph is y=-3(√2x)-4 and y=-3√(x-4) the transformation would be:
</span><span>The graph is compressed horizontally by a factor of 2
x=1/2x'
</span>y=-3(√2x)-4
y=-3(√x')-4 <span>
</span><span>moved left 4
x=x'-4
</span>y=-3(√x)-4
y=-3(√x'-4)-4
<span>
moved down 4
y=y'-4
</span>y=-3(√x-4)-4
y'-4=-3(√x'-4)-4
y'=-3(√x'-4)-4 +4
y'=-3(√x'-4)
Answer: C. <span>The graph is compressed horizontally by a factor of 2, moved left 4, and moved down 4.
</span>
Answer:
263-5000=4737
Step-by-step explanation:
Answer:
send the graph and ill solve it
Step-by-step explanation: